Определение параметров вращения солнечной атмосферы по асимметрии фраунгоферовых линий - Гадун, А.С.; Пикалов, К.Н. (Кинематика и физика небесных тел, 1990)
Определены параметры вращения Солнца по асимметрии и по центральным глубинам линий поглощения. Проведен анализ влияния вращения на глубины и асимметрию спектральных линий. Сделан вывод о перспективности нового подхода к определению скорости вращения медленно вращающихся звезд по асимметрии их спектральных линий. The solar rotation velocity has been found from comparison of central depths and asymmetries of Fraunhofer lines in the spectrum of the Sun as a star with central depths and asymmetries of the same lines at different distances from solar centre. The effect of rotation on line asymmetries and line central depths was studied. The conclusion is made that the new method may be used for the determination of the rotation rate of slow rotating stars from the comparison of line asymmetries at different distances from the stellar disk centre (using the multidimensional convective models).